Understanding the Clean Air Act: Implementation Issues for Electric Utilities - Dudley, Susan (Maine Policy Review, 1993)
With the creation of tradable sulfur dioxide permits under the Clean Air Act Amendments of 1990, financial markets have been drawn into the effort to achieve targeted air pollution reductions at least cost. As Susan Dudley explains, financial markets will go well beyond simply providing a place to buy and sell permits. These markets will create a variety of "futures" contracts that will enable utilities to manage the risks of planning future strategies to control pollution.
Keywords: Clean Air Act; electric utilities